Associating Time Devoted to Online Gaming with Subjective Well-being, Emotional States and Affective Schedules - Damir Vučić; Violeta Vidaček-Hainš; Sanja Ćurković (Journal of Information and Organizational Sciences)
Online gaming is one of the most popular students’ activities associated with various aspects of their experience and behavior. This paper aims to investigate the frequency of online gaming among students and determine the association among the frequency of online gaming, emotional states, and affective schedules. The sample included 1000 undergraduate and graduate students at the University of Zagreb, studying in different science fields. The average age of the respondents was 23. The self-evaluation of time that students devote to online gaming was conducted in accordance with time categories expressed in hours devoted to online gaming. The subjective well-being was based on the self-assessment of life satisfaction questionnaire, the assessment of the frequency and intensity of unpleasant emotional state on DASS-21 questionnaire and a measure of the assessment of positive and negative affect on PANAS (Positive-PA and Negative-NA affective Schedule. The results confirm that students who are excessively involved in online gaming are less satisfied with their lives, assess unpleasant affective experience more intensively and pleasant affective experience less, compared to students who are less frequently involved in online gaming. Female students assess unpleasant emotional states of anxiety, depression, and stress more intensively than male students. Furthermore, female students assess unpleasant and pleasant affective experience more intensively than male students. These results can be applied to provide suggestions on what optimum time devoted to online gaming compared to other activities would be.